2019
DOI: 10.1053/j.gastro.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s Disease Exclusion Diet Plus Partial Enteral Nutrition Induces Sustained Remission in a Randomized Controlled Trial

Abstract: See Covering the Cover synopsis on 269. See editorial on page 295. BACKGROUND & AIMS: Exclusive enteral nutrition (EEN) is recommended for children with mild to moderate Crohn's disease (CD), but implementation is challenging. We compared EEN with the CD exclusion diet (CDED), a whole-food diet coupled with partial enteral nutrition (PEN), designed to reduce exposure to dietary components that have adverse effects on the microbiome and intestinal barrier. METHODS: We performed a 12-week prospective trial of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
562
4
43

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(661 citation statements)
references
References 33 publications
10
562
4
43
Order By: Relevance
“…A newly published RCT (July 2019) by the same research group adds further support to use of this novel nutritional therapy. Levine et al . demonstrate that, although there was no significant difference in the number of patients entering remission by week 6, the CDED with PEN ( n = 40) was better tolerated than EEN ( n = 34), with a significantly lower dropout rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A newly published RCT (July 2019) by the same research group adds further support to use of this novel nutritional therapy. Levine et al . demonstrate that, although there was no significant difference in the number of patients entering remission by week 6, the CDED with PEN ( n = 40) was better tolerated than EEN ( n = 34), with a significantly lower dropout rate.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrate that, although there was no significant difference in the number of patients entering remission by week 6, the CDED with PEN ( n = 40) was better tolerated than EEN ( n = 34), with a significantly lower dropout rate. It was also suggested that the CDED could be superior to EEN in terms of sustaining remission, with a significantly greater proportion of the CDED group having a PCDAI <10 at week 12 compared to the EEN . Alternative dietary treatment options to EEN are certainly a growing area of interest, with another research team having also recently published their findings after examining a completely solid food‐based diet as opposed to PEN alongside a specialised diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, so-called anti-inflammatory diets that attempt to recapitulate the nutritional contents of EEN while still providing essentially normal foods have been published. [137][138][139] The mechanisms by which EEN result in improvement are unclear; although the microbiota is altered, this is not necessarily responsible for the clinical improvement, as the alteration may actually make the microbiota even more dysbiotic as evidenced by lower alpha diversity and lower fecal abundance of F prausnitzii. 140 EEN is the only dietary approach for which there are published data in JIA.…”
Section: Dietary Therapymentioning
confidence: 99%
“…The etiology of IBD is unclear, involving a complex interplay between mucosal immunity, environment, and the gut microbiota . Evidence‐based dietary interventions are used to induce clinical remission and alleviate mucosal inflammation in children with IBD and allow better symptom management, decrease relapse rates, and offer cost‐effective low risk disease management . A western diet high in meats, cheese, and n ‐6 polyunsaturated fatty acids (PUFAs), but low in plants and n ‐3 PUFAs, promotes mucosal inflammation and the growth of enterobacteria, including adherent‐invasive Escherichia coli implicated in IBD .…”
Section: Introductionmentioning
confidence: 99%